Evaluasi Perbandingan Ranking Antara Proposed Value dan Perceived Value Terhadap E-Commerce Berdasarkan Model UX Honeycomb - Ressya Sukma; Hanifah Muslimah Az-zahra; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-commerce or electronic commerce is a process of selling and buying digitally. Its fast development is followed by the high internet usage in Indonesia. Lazada, Tokopedia, dll are ones of existing e-commerce that are most-used in Indonesia. These 5 applications offers 5 values for the users which in fact, still have certain lacks. This research is held with means to analyze value given by these 5 most-used e-commerce applications. To evaluate the values of these e-commerce applications, this research applies UX Honeycomb method which is a tool with 7 value terms which are useful, usable, findable, credible, desirable,accessible, valueable. These values is used to explain the quality of users' experience.The result of comparing proposed value and perceived value of the applications is the needs to increase credibility for Lazada, desirability and usability for Tokopedia, and desirability and usability for Mataharimall. In the other hand, the 7 values of Bukalapak and Zalora have been successfully perceived by the users.